SELF-EFFICACY SEBAGAI MEDIASI UNIVERSITY ENVIRONMENT SUPPORT DAN ENTREPRENEURIAL INTENTION PADA MAHASISWA PROGRAM BISNIS ENTREPRENEURSHIP - Krismi Budi Sienatra (Business Management Journal, 2021)
The high number of demographic bonus in Indonesia does not match the number of entrepreneurs in that country. Indonesia has the lowest percentage of entrepreneurs compared to other countries. One of the ways to increase the number percentage of entrepreneurs in Indonesia is to create an entrepreneur especially through students. The intention of students in entrepreneurship can be increased through the support that is given by the university. The main purpose of learning to attempt to create a young entrepreneur in the community environment through problem and project-based-learning system that is trusted to be able to increase student’s self-efficacy and entrepreneurial intention. Therefore, the purpose of this research is to find out the effect of university environment support on entrepreneurial intention through self-efficacy as mediation. This research uses quantitative approach by using Partial Least Square. The sampling technique that is used is random sampling with the total sample of 82 final year students. The research results show that university environment support does not affect significant on entrepreneurial intention, university environment support affects significant on self-efficacy, self-efficacy affects significant on entrepreneurial intention, self-efficacy mediates the effect of university environment support and students’ entrepreneurial intention.